Spoonbenders - Gregory, Daryl (Alfred A. Knopf, 2017)
"A generations-spanning family of psychics--both blessed and burdened by their abilities--must use their powers to save themselves from the CIA, the local mafia, and a skeptic hell-bent on discrediting them in this hilarious, tender, magical novel about the invisible forces that bind us. The Telemachus family is known for performing inexplicable feats on talk shows and late-night television. Teddy, a master conman, heads up a clan who possess gifts he only fakes: there's Maureen, who can astral project; Irene, the human lie detector; Frankie, gifted with telekinesis; and Buddy, the clairvoyant. But when, one night, the magic fails to materialize, the family withdraws to Chicago where they live in shame for years. Until: As they find themselves facing a troika of threats (CIA, mafia, unrelenting skeptic), Matty, grandson of the family patriarch, discovers a bit of the old Telemachus magic in himself. Now, they must put past obstacles behind them and unite like never before. But will it be enough to bring The Amazing Telemachus Family back to its amazing life?"--